Asymptotic method for the investigation of m-frequency oscillation systems - Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We describe an asymptotic method for the integration of m-frequency oscillation systems of order 2n, analyze averaged equations in nonresonance and resonance cases, prove a theorem on the preservation of smooth p-dimensionai invariant tori under perturbation for any 0 ≤ p ≤ n, and indicate forms of decomposable m-frequency oscillation systems.